An Opinion on Soft Power - E. M. Astakhov (Vestnik MGIMO-Universiteta)
The article analyzes different aspects of the "soft power" of Russia. The author affirms that in this field the country doesn't have well defined strategies policy. To Russia has the excellent potential for the promotion of its positive image. This potential is primarily due to the famous Russian science, literature, music and art. But this "natural"potential has to be used in the national interests abroad. In recent years the Russian government has made some important steps in cultural diplomacy, in particular for the promotion of Russian language and supporting Russian Diaspora. However, much more has to be done not only in these directions, but also in propaganda and counterpropaganda to meet information pressure against Russia. In this connection, to form properly all directions of the policy of "soft power", is desirable to use the experience of other countries. The states who pretend to have an important place in the world, consider "soft power" as a strategic policy aiming to strengthen their geopolitical positions. In this context the author offers some suggestions concerning different organizational aspects. Special attention is given to the coordination of the activities of all structures involved in the policy of "soft power ".